Summertime Tintinnid Community in the Surface Waters Across the North Pacific Transition Zone - Li, Haibo; Xuan, Jun; Wang, Chaofeng; Chen, Zhaohui; Grégori, Gérald; Zhao, Yuan; Zhang, Wuchang (Frontiers in Microbiology, 2021)
Located from 35-45 latitude in both hemispheres, the transition zone is an important region with respect to the planktonic biogeography of the sea. However, to the best of our knowledge, there have been no reports on the existence of a tintinnid community in the transition zone. In this research, tintinnids along two transects across the North Pacific Transition Zone (NPTZ) were investigated in summer 2016 and 2019. 83 oceanic tintinnid species were identified, 41 of which were defined as common oceanic species. The common oceanic species were further divided into 5 groups: boreal, warm water type I, warm water type II, transition zone and cosmopolitan species. Undella californiensis and U. clevei were transition zone species. Other species, such as Amphorides minor, Dadayiella ganymedes, Dictyocysta mitra, Eutintinnus pacificus, E. tubulosus, Protorhabdonella simplex and Steenstrupiella steenstrupii, were most abundant in the NPTZ but spread over a much larger distribution region. Species richness showed no obvious increase in the NPTZ. Boreal, transition zone and warm water communities were divided along the two transects. Tintinnid transition zone community mainly distributed in regions with water temperatures between 15 and 20C. The tintinnid LOD (lorica oral diameter) size classes were dominated by the 24-28 m size class in three communities, but the dominance decreased from 66.26% in the boreal community to 48.85% in the transition zone community and then to 22.72% in the warm water community. Our research confirmed the existence of tintinnid transition zone species and community. The abrupt disappearance of warm water type I species below 15C suggested that this group could be used as an indicator of the northern boundary of the NPTZ.